Reconnaissance à travers les montagnes Mackenzie sur les rivières Pelly, Ross et Gravel, Yukon et territoires du Nord-Ouest. - Keele, Joseph, 1863-1923.; Geological Survey of Canada. (Ottawa, Imprimerie du governement, 1914)
Issued also in English. At head of title: Canada. Ministère des mines . Commission géologique, Canada. Mode of access: Internet. In lower right corner of t.-p.: no. 1098.